Greece and Rome in Israeli Schools. - Baratz, Amit (Scripta Classica Israelica, 2023)
This article surveys the ancient Greek and Roman sources that are taught in Israel from middle school (ages 12-15) to high school (ages 15-18). The mandatory subjects in which these texts are studied are literature and history, to which I add one optional course in philosophy. 2022 was a year of reform in high school humanities. The article presents the classical material studied in Israeli schools both before and after the reform.